Control of Type II Diabetes, Its Relationship with Obesity and Basal Metabolic Rate - Faiza Kamal; Rozina Arshad; Bilal Bin Younis; Rashid Ahmed; Zakia Noureen; Muhammad Ahmad (Shalamar Medical & Dental College, Lahore, Pakistan, 2019)
Background: The prevalence of T2DM is around 7-10%. Control of diabetes and factors influencing it in third world countries need to be clearly defined as most of the people have poor glycemic control. Methods: A cross sectional study was conducted and purposive sampling was done to collect data for 5 months. A total of 766 type 2 diabetic patients were enrolled who visited SiDER (Sakina Institute of Diabetes and Endocrine Research Center) at Shalamar Hospital, Lahore, Pakistan. Only pre-diagnosed diabetic subjects with a random blood glucose of more than 200mg/dl at two occasions and fasting blood glucose levels more than 126mg/dl were included in the study. Variables like Body Mass Index (BMI), Glycated Hemoglobin (HbA1c) and Basal Metabolic Rate (BMR) were recorded. The data was analyzed by SPSS 22 version. Results: A total of 766 diabetics were recruited in the study out of which 40.3% were male and 59.7% were females. The mean age was 48.72±10.43 years. Out of these 53.39% were obese, 32.64% were overweight and only 13.97% had a normal body mass index BMI). HbA1c levels in the sample population showed that only 13.05% had very healthy control i.e. 7% or less. There was a positive co-relation between Body Mass Indexand glycemic control. However there was no statistically significant relation between Basal Metabolic Rateand glycemic control. Conclusion: People with high Body Mass Index were found to have suboptimal glycemic control. It was also observed that higher percentage of diabetic patients fall in age group of 41-55 years. More powerful studies are needed to establish a relation between glycated hemoglobin and Basal Metabolic Rate.